MINIMALLY INVASIVE DECOMPRESSION INTERVENTIONS IN THE TREATMENT OF ACUTE CHOLECYSTITIS IN ELDERLY AND SENILE PATIENTS - Kim Yang Jou, Ya. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. This article presents information on the variant of the clinical course of acute cholecystitis in elderly and senile patients using various approaches to surgical and conservative treatment. Material. It is substantiated that active surgical tactics, supplemented by the implementation of minimally invasive decompression echo-controlled interventions according to the formulated indications, can significantly improve the immediate results of treatment of patients with acute cholecystitis of older age groups. Conclusion. The use of minimally invasive decompression echo-controlled interventions is an effective and safe way to treat acute cholecystitis in patients of older age groups with high surgical and anaesthetic risk. Active surgical tactics in acute cholecystitis supplemented using minimally invasive decompression echo-controlled interventions, can significantly improve both immediate and long-term results treatment in patients with acute cholecystitis of older age groups and reduce postoperative mortality from 13.5% to 3.7%, overall mortality from 10.2% to 1.6%.